Perineal support and risk of obstetric anal sphincter injuries: a Delphi survey. (30th December 2014) - Ismail, Khaled M. K.; Paschetta, Elena; Papoutsis, Dimitrios; Freeman, Robert M.
Abstract Objective To explore the views of a multidisciplinary group of experts and achieve consensus on the importance of perineal support in preventing obstetric anal sphincter injuries (OASIS). Design A three‐generational Delphi survey. Setting A UK‐wide survey of experts. Population A panel of 20 members consisting of obstetricians, midwives and urogynecologists recommended by UK professional bodies. Methods A 58‐item web‐based questionnaire was sent to all participants who were asked to anonymously rate the importance of each item on a six‐point Likert scale. They were asked to rate their level of agreement on statements related to hands‐on/hands‐poised techniques, the association of hands‐poised/hands‐off approach with OASIS, the need to implement perineal support and the need to improve the evidence to support it. Systematic feedback of responses from previous rounds was provided to participants. Main outcome measures To achieve consensus on key areas related to perineal support. Results The response rate was 100% in all three iterations. There was consensus that current UK practice regarding perineal protection was not based on robust evidence. The respondents agreed that hands‐poised/hands‐off and OASIS are causally related and that hands‐poised was misinterpreted by clinicians as hands‐off. Although 90% of experts agreed that some form of randomized trial was required and that all would be prepared to take part, there was also consensus (75%) that in the meantime, hands‐on should be the recommended technique. Conclusions Our results highlight the current lack of evidence to support policies of perineal support at time of birth and the need to address this controversial issue.